PRODUCTION PERFORMANCE OF QUAIL (Coturnix-coturnix japonica) AND IDENTIFICATION OF IgY CONCENTRATION IN BLOOD SERUM AND YOLK - Tarigan, Indri Nur Krisna; Afnan, Rudi; Murtini, Sri; Ulupi, Niken (Jurnal Kedokteran Hewan, 2024)
This research was conducted to provide information on the production performance of quail parent stock and its offspring with various IgY concentrations. A total of 42 female quail parents stock aged five weeks old were used in this study. Five quails were categorized as medium IgY group with concentrations of 431.12-531.87 g/mL and 37 quails were categorized as low IgY group with concentration of 251.87-384.68 g/mL. The variables observed were the production performance such as initial body weight, feed intake, final body weight, body weight gain, number of eggs, egg mass, egg weight, egg laying intensity, feed conversion, morbidity, and mortality rate and IgY concentration of the yolk of the offsprings. Production performance of female quail with different concentrations of IgY was not significantly different (P0.05). IgY concentration of offsprings in egg yolk was also not significantly different (P0.05) in both groups. The results showed that female quails parent stock with low blood IgY showed better production. Meanwhile, female quail parents stock with moderate blood IgY concentrations produced offspring with high-maternal IgY concentrations in yolk.